Efeito do treinamento auditivo computadorizado nas habilidades auditivas e de fala em crianças com transtornos dos sons da fala - Valim, Cristiane Dellinghausen (2023)
Objective: to measure the effect of computerized auditory training (CAT) on behavioral auditory and speech skills in children with Speech Sound Disorder (SSD). Method: this is a prospective quantitative longitudinal study of a clinical-experimental nature and 14 children of both sexes (11 boys and three girls), aged between 6 and 9 years old, diagnosed with SSD who were in speech therapy or on a waiting list for it. All children were assessed auditorily and showed one or more altered auditory skills in the behavioral assessment of Central Auditory Processing (CAP). They underwent a complementary therapeutic approach through CAT. The CAT adopted, mediated by the use of Escuta Ativa® software, included 12 activities divided into six sessions that aim to work on auditory skills in a challenging way, termed as Brief-CAT. The subjects were evaluated pre and post-intervention regarding their auditory skills using the behavioral assessment of CAP, speech using the INFONO software – Phonological Assessment Instrument and the APDQ – Auditory Processing Domains Questionnaire questionnaire was applied to measure the parents' perception of the behavior hearing of the children evaluated. Inferential analysis of the data was carried out. Results: in the quantitative analysis, the adopted CAT had an effect on figure-ground skills for verbal sounds. No statistically significant changes were observed in the temporal resolution ability. When observing the CAP behavioral tests individually in a qualitative way, they all showed an evolution in terms of the number of subjects who changed their profile from “altered” to “normal”, even if not all of them normalized the assessment as a whole. When analyzing the effect of CAT on the variables: “speech therapy for SSD” (with or without speech therapy) and “type of SSD” (Phonological or Motor), no clinically relevant influences were observed on the results of the behavioral assessment of CAP after the intervention adopted. The APDQ questionnaire maintained the same results after the intervention. When analyzing the speech data, post TAC, a significant difference was observed between children with and without speech therapy regarding the evolution of the phonological system (number of absent and acquired sounds) and the reduction in the severity of SSD. The Brief-CAT impacted speech results according to the type of SSD, as results were significant for children with SSD in aspects of fewer absent sounds, more acquired sounds in the phonological system, higher Percentage of Correct Consonants, and consequently, lower severity of SSD. Conclusion: Brief-CAT had an effect on the figure-background auditory skill of children with SSD, promoting an improvement in the scores of most of the CAP behavioral assessment tests, even though the delay of the CAP or CAPD is still characterized in some subjects. The variables “speech therapy for SSD” and “type of SSD” did not suffer clinical influence after the Brief-CAT. Parents' perception regarding the auditory behavior of the children evaluated did not change in the preand post-intervention responsesThe effects of Brief-CAT on the evolution of speech in the children of this study lead to the conclusion that speech therapy combined with CAT should be the most suitable therapeutic indication, evidenced in the evolution of the phonological system and reduction in the severity of SSD. Children with Phonological SSD showed better speech results compared to those with Motor SSD.